Engagement, bonding, and identity across multiple platforms: Avaaz on Facebook, YouTube, and MySpace - Kavada, Anastasia (MedieKultur: Journal of media and communication research, 2012)
This article explores the role of social media platforms in transnational activism by examining the case of Avaaz.org, an international advocacy organization aiming to bring people-powered politics to global decision-making. Focusing on the Avaaz website, its channel on YouTube, its page on Facebook and its profile page on MySpace, the article investigates the affordances of these platforms for identity-building, bonding, and engagement. The empirical data is derived from features analysis of the selected web platforms, as well as textual analysis of the comments posted by users. The findings show that while social media platforms make individual voices more visible, their design helps Avaaz to maintain a coherent collective voice. In terms of bonding, platforms allow individual activists to communicate with the organization and to spread its message to their existing social networks, but opportunities for private interpersonal communication with other Avaaz supporters are limited.